Acute effects of glucagon‐like peptide‐1, GLP‐19–36 amide, and exenatide on mesenteric blood flow, cardiovascular parameters, and biomarkers in healthy volunteers. Issue 4 (24th February 2017) - Bremholm, Lasse; Andersen, Ulrik B.; Hornum, Mads; Hilsted, Linda; Veedfald, Simon; Hartmann, Bolette; Holst, Jens Juul
Abstract: Glucagon‐like peptide‐1 (GLP‐1, GLP‐17–36amide ) and its sister peptide glucagon‐like peptide 2 (GLP‐2) influence numerous intestinal functions and GLP‐2 greatly increases intestinal blood flow. We hypothesized that GLP‐1 also stimulates intestinal blood flow and that this would impact on the overall digestive and cardiovascular effects of the hormone. To investigate the influence of GLP‐1 receptor agonism on mesenteric and renal blood flow and cardiovascular parameters, we carried out a double‐blinded randomized clinical trial. A total of eight healthy volunteers received high physiological subcutaneous injections of GLP‐1, GLP‐19–36 amide (bioactive metabolite), exenatide (stable GLP‐1 agonist), or saline on four separate days. Blood flow in mesenteric, celiac, and renal arteries was measured by Doppler ultrasound. Blood pressure, heart rate, cardiac output, and stroke volume were measured continuously using an integrated system. Plasma was analyzed for glucose, GLP‐1 (intact and total), exenatide and Pancreatic polypeptide (PP), and serum for insulin and C‐peptide. Neither GLP‐1, GLP‐19–36 amide, exenatide nor saline elicited any changes in blood flow parameters in the mesenteric or renal arteries. GLP‐1 significantly increased heart rate (two‐way ANOVA, injection [ P  = 0.0162], time [ P  = 0.0038], and injection × time [ P  = 0.082]; Tukey post hoc GLP‐1 vs. saline and GLP‐19–36amide [ P  < 0.011]), and tended to increase cardiac output and decrease stroke volume compared to GLP‐19–36 amide and saline. Blood pressures were not affected. As expected, glucose levels fell and insulin secretion increased after infusion of both GLP‐1 and exenatide. Abstract : In healthy volunteers, we investigated the effects of GLP‐1 (7–36), GLP‐1 (9–36), and exenatide on mesenteric blood flow. Contrary to what we had expected, mesenteric blood flow did not increase.